Design of Distributor Performance Measurement System Using Balanced Score Card Method - Apriliyanto, Deri; Syairudin, Bambang (Journal La Multiapp, 2025)
The research designs an extensive performance measurement system for distributors of PT Semen Indonesia Tbk by employing the Balanced Scorecard (BSC) methodology. The research examines how the company has struggled to reach Revenue, Sales Volume and EBITDA targets because bulk cement sales experienced a 13.5% rise in demand yet did not fulfill RKAP expectations. The research targets distributor performance assessment since distributors substantially boost company sales beyond direct sales activities. BSC provides organizations with a method to create distributor-level metrics that support corporate objectives through financial and customer and internal process and learning and growth criteria. The study extends key performance indicators (KPIs) from the Corporate Sales Group through multiple levels to distributor performance metrics which include volume while measuring revenue together with market share and customer satisfaction as well as operational efficiency. The introduction of this system during 2024 effectively boosted distributor performance through its 101.6% success in meeting sales targets along with 0.2% higher market share achievement. The research offers final recommendations that support ongoing personnel training as well as periodic KPI socialization alongside plans for additional studies to advance performance assessment systems across the Corporate Sales Group.